Post-traumatic stress disorder, depression and the associated factors among children and adolescents with a history of maltreatment in Uganda - Ainaman, Herbert E.; Weierstall-Pust, Roland; Bahati, Ronald; Otwine, Anne; Tumwesigire, Sam; Rukundo,Godfrey Zari (European journal of psychotraumatology, 2022)
Worldwide, children who grow up under adverse conditions risk the development of mental health problems. However, reliable data on the estimated magnitude of mental disorders of PTSD, depression and their associated factors among maltreated children and adolescents in low- and middle-income-countries (LMICs) is still lacking. This study estimated the magnitude of PTSD, depression and the associated factors among the children and adolescents with a history of maltreatment in Southwestern Uganda. Methods: In this cross-sectional study, we assessed 232 children and adolescents on the prevalence of PTSD using Child PTSD Symptoms Scale for DSM-5 – Self-Report (CPSS-VSR) and Depression using the Center for Epidemiological Studies Depression Scale for Children (CES-DC). Predictor variables were taken from the Maltreatment and Abuse Chronology of Exposure- Paediatric Version (Pedi MACE). Logistic regressions analyses were selected for statistical modelling while odds-ratios were calculated to assess the strength of associations between the predictor and outcome variables. Results: In total, 140 (60%) participants fulfiled diagnostic criteria for PTSD and 91 (39%) for depression respectively. Predictor variables of PTSD were witnessing intimate partner violence (OR = 1.48, 95% CI: 1.19–1.83, p = <0.001), having lived in more than two homes (OR = 2.69, 95%CI: 1.34–5.41, p = .005), and being cared for by non-relatives (OR = 2.25; 95%CI: 2.26–223.9, p = .008). Variables predicting depression were witnessing intimate partner violence (OR = 1.30; 95%CI: 108–1.57, p = .006); being cared for by non-relatives (OR = 5.62, 95%CI: 1.36–23.1, p = .001) and being female (OR = .054, 95% CI: 0.30–1.00, p = .005). Conclusion: Children living under adverse conditions are at a higher risk of developing PTSD and depression. We recommend interventions that aim at reducing adverse psychosocial stressors so as to improve or restore the children’s mental health. Abbreviations: PTSD: Post traumatic stress disorder; LMICs: Low- and middle-income countries; IPV: Intimate partner violence; OVC: Orphans and vulnerable children
Keywords: Adolescents; Children; Depression; Maltreatment; PTSD; Uganda